Transient anode voltage modeling of IGBT and its base doping profile investigation - Das, Avijit; Md Ziaur Rahman, Khan (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 18th International Conference on Computer and Information Technology, ICCIT 2015; Military Institute of Science and Technology (MIST) Mirpur Cantonment Dhaka; Bangladesh; 21 December 2015 through 23 December 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/ICCITechn.2015.7488054